Human Proangiogenic Circulating Hematopoietic Stem and Progenitor Cells Promote Tumor Growth in an Orthotopic Melanoma Xenograft Model - Mund, Julie A. (2013)
We previously identified a distinct population of human circulating hematopoietic stem and progenitor cells (CHSPCs; CD14(-)glyA(-)CD34(+)AC133(+/-)CD45(dim)CD31(+) cells) in the peripheral blood (PB) and bone marrow, and their frequency in the PB can correlate with disease state. The proangiogenic subset (pCHSPC) play a role in regulating tumor progression, for we previously demonstrated a statistically significant increase in C32 melanoma growth in NOD.Cg-Prkdc(scid) (NOD/SCID) injected with human pCHSPCs (p<0.001). We now provide further evidence that pCHSPCs possess proangiogenic properties. In vitro bio-plex cytokine analyses and tube forming assays indicate that pCHSPCs secrete a proangiogenic profile and promote vessel formation respectively. We also developed a humanized bone marrow-melanoma orthotopic model to explore in vivo the biological significance of the pCHSPC population. Growth of melanoma xenografts increased more rapidly at 3-4 weeks post-tumor implantation in mice previously transplanted with human CD34(+) cells compared to control mice. Increases in pCHSPCs in PB correlated with increases in tumor growth. Additionally, to determine if we could prevent the appearance of pCHSPCs in the PB, mice with humanized bone marrow-melanoma xenografts were administered Interferon α-2b, which is used clinically for treatment of melanoma. The mobilization of the pCHSPCs was decreased in the mice with the humanized bone marrow-melanoma xenografts. Taken together, these data indicate that pCHSPCs play a functional role in tumor growth. The novel in vivo model described here can be utilized to further validate pCHSPCs as a biomarker of tumor progression. The model can also be used to screen and optimize anticancer/anti-angiogenic therapies in a humanized system.